Generation and characterization of ultrathin free-flowing liquid sheets - Jake D. Koralek (Nature Portfolio, 2018)
X-ray spectroscopy is a tool used for the investigation of aqueous solutions but the strong absorption of water means that very thin liquid sheets are needed for accurate analysis. Here the authors produce free-flowing liquid sheets 2 orders of magnitude thinner than sheets obtained with existing techniques.